Teamwork and E-learning as a New Approach in High Education - Danijela Kardaš; Bojan Knežević; Petar Gvero (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
Team work has become a central issue for many corporations, and self-managing teams are often viewed as the goal of team work development programs. The increased pressure on professionals to perform their tasks with fewer employees, at faster speeds, and with more quality and customer responsiveness creates the need for team work. In modern society and working place, dispersed teams are increasingly common in both large and small organizations. There are wide varieties of communication and collaboration options available. One of these is also using multifunctional rooms (MFR). This paper analyses introducing of a course “Team Project” on the first and second cycle of studies at University in Banja Luka, Faculty of Mechanical Engineering and using MFR as a tool in learning process. Introduction of this course and establishment of MFR came as a transfer of the knowledge, experience and technology from NTNU (Norwegian University of Science and Technology) to the Faculty of Mechanical Engineering within the project HERD QIMSEE (HERD Quality Improvement of Master Programs in Sustainable Energy and Environment). “Team Project” is experience - based learning course where students learn how to be a part of a team and work on multidisciplinary problems. MFR is used as a tool in this process.
Keywords: I23; 330; teamwork; skills; multidisciplinary; education; multifunctional room